2019
DOI: 10.1051/0004-6361/201834741
|View full text |Cite
|
Sign up to set email alerts
|

Be and O in the ultra metal-poor dwarf 2MASS J18082002-5104378: the Be–O correlation

Abstract: Context. Measurable amounts of Be could have been synthesised primordially if the Universe were non-homogeneous or in the presence of late decaying relic particles. Aims. We investigate the Be abundance in the extremely metal-poor star 2MASS J1808-5104 ([Fe/H]=-3.84) with the aim of constraining inhomogeneities or the presence of late decaying particles. Methods. High resolution, high signal-to-noise ratio UV spectra were acquired at ESO with the Kueyen 8.2 m telescope and the UVES spectrograph. Abundances wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 76 publications
(121 reference statements)
7
30
0
Order By: Relevance
“…A similar possibility of increased scatter at low metallicities was discussed by Spite et al (2019), but mainly relied on the relation between log(Be/H) and [O/H]. Unfortunately, we cannot derive reliable oxygen abundances here, as they require the use of three-dimensional hydrodynamical models.…”
Section: Early Enrichment In Ironmentioning
confidence: 74%
See 1 more Smart Citation
“…A similar possibility of increased scatter at low metallicities was discussed by Spite et al (2019), but mainly relied on the relation between log(Be/H) and [O/H]. Unfortunately, we cannot derive reliable oxygen abundances here, as they require the use of three-dimensional hydrodynamical models.…”
Section: Early Enrichment In Ironmentioning
confidence: 74%
“…The evidence supporting the flattening of the relation was made weaker by the upper limit of the Be abundance in BD+ 44 493, a star with [Fe/H] = −3.7, derived by Ito et al (2009Ito et al ( , 2013 and later refined by Placco et al (2014). Similar evidence against the flattening is given by the more recent Be upper limit for star 2MASS J1808-5104 (Spite et al 2019). In both cases, the inferred limits are below the level of the possible plateau.…”
Section: Introductionmentioning
confidence: 75%
“…It could simply be that this system is one that significantly deviates from the Galactic Be-O relation. Spite et al (2019) found that 2MASS J1808-5104, which has a similar [Fe/H] but lower [O/H] than CS 22876-32, has no detectable Be and its upper limit lies well below the Galactic Be-O line. Another similar case is the CEMP-no star BD +44 • 493 (Ito et al 2013), again a similar [Fe/H] and no detectable Be.…”
Section: Discussionmentioning
confidence: 97%
“…8 at the lowest T eff and are Li depleted, but with measurable Li. The explanation suggested by Spite et al (2019) for these stars was that their age is old enough that cosmic rays did not have enough time to build significant quantities of Be. New higher-quality observations of Be in CS 22876-32 would be very valuable, since they would allow us to establish if this system lies on the Galactic Be-O line or if it is below the line, like 2MASS J1808-5104 and BD +44 • 493.…”
Section: Discussionmentioning
confidence: 99%
“…Quite unexpectedly, the most metal-poor star known, SDSS J1029+1729, is on a thick-disc orbit (Caffau 2018;Sestito et al 2019;Di Matteo et al 2020). Another extremely metal-poor star 2MASS J18082002-5104378 (Meléndez et al 2016) with an iron abundance [Fe/H] = −3.84 (Spite et al 2019) is on a thin-disc orbit (Schlaufman et al 2018;Sestito et al 2019;Di Matteo et al 2020). More generally it now appears that when a sample of stars is chemically selected as metal poor there is always a significant fraction that is on disc orbits (see e.g.…”
Section: Introductionmentioning
confidence: 99%